2010
DOI: 10.1007/s11401-008-0417-y
|View full text |Cite
|
Sign up to set email alerts
|

Operations on 3-dimensional small covers

Abstract: The purpose of this paper is to study relations among equivariant operations on 3-dimensional small covers. The author gets three formulas for these operations. As an application, the Nishimura's theorem on the construction of oriented 3-dimensional small covers and the Lü-Yu's theorem on the construction of all 3-dimensional small covers are improved. Moreover, for a construction of 3-dimensional 2-torus manifolds, it is shown that all operations can be obtained by using the equivariant surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In addition, Kuroki [6] studied the relations among six operations v , e , eve , , , c on P and found that e = • ( v P 3 (3)) and eve = 2 • ( v P 3 − (3)). Furthermore, Nishimura [11] discovered more relations among the operations in Theorem 5.5 and obtained another algebraic system by the following theroem, which improved Theorem 5.5.…”
Section: 2mentioning
confidence: 99%
“…In addition, Kuroki [6] studied the relations among six operations v , e , eve , , , c on P and found that e = • ( v P 3 (3)) and eve = 2 • ( v P 3 − (3)). Furthermore, Nishimura [11] discovered more relations among the operations in Theorem 5.5 and obtained another algebraic system by the following theroem, which improved Theorem 5.5.…”
Section: 2mentioning
confidence: 99%
“…If k = 1, then the projective characteristic function is the ordinary characteristic function, i.e., the fibre dimension is 0. Therefore, we can regard the 0-dimensional projective fibre sum ♯ ∆ 0 as the ordinary (equivariant) connected sum ♯ appeared in [12,13,17,24].…”
Section: Combinatorial Interpretation Of the Fibre Summentioning
confidence: 99%
“…Then M is generated by the classes of S 1 ×RP 2 over the 3-sided prism and RP 3 over the 3-simplex ( [12,14]). Much further research on small covers over the 3-sided prism has been carried on ( [11,16]). An example of a cohomologically non-rigid polytope was obtained from a 3-sided prism by iterating the operation of vertex cut twice ( [8]).…”
Section: Introductionmentioning
confidence: 99%